A Review on Chunnam an Effective Siddha Higher Order Medicine - Indrakumar, Nithyamala; V, Shalini; C, Nithya; ., Karpagavalli; A, Mariappan; G, Senthilvel; R, Meenakumari (International Journal of Membrane Science and Technology, 2023)
Siddha’s system of medicine is one of the ancient systems of medicine including a lot of research data without scientific evidence. Siddha medicine has 32 types of internal medicines and 32 types of external medicines which includes 24 different processes. Siddha system of medicine has a huge number of medicinal preparations it possesses very effective principles to treat various ailments with minimal side effects. Chunnam (Calcinated nanoparticle powder) is one of the 32 types of internal medicine in Siddha. Chunnam is white in color. Chunnam is prepared from metals, minerals, and marine products. Chunnam like higher-order medicine has more therapeutic value minimal dose. In Chunnam preparation, mercury paadaana or metals are triturated either individually or combined by adding herbal juices (depending on the preparation) then kept in the crucible and sealed with mud-pasted cloth. Then they are blown and made into white powders and then it was cooled and stored in an airtight glass container. The Siddha higher-order medicine Chunnam is a very highly acclaimed unique dosage form it was in an alkaline group of drugs that is indicated for chronic diseases. Chunnam such as Thaalaga chunnam, Sangu sunnam, Pavala veera chunnam, Mutthu chunnam, Padigara chunnam, Nandukkal chunnam etc. It is used for the treatment of chronic diseases like leprosy, tuberculosis, cancer, urolithiasis, etc, This review article attempts to facilitate the Chunnam preparations mentioned in Siddha literature, and its applications were explained broadly.